Epigenetic therapy upregulates the tumor suppressor microRNA-126 and its host gene EGFL7 in human cancer cells - Saito, Yoshimasa; Friedman, Jeffrey M.; Chihara, Yoshitomo; Egger, Gerda; Chuang, Jody C.; Liang, Gangning (Biochemical and biophysical research communications, 2009)
Studies have shown that aberrant expression of miRNAs is involved in the initiation and progression of cancer, and several miRNAs have been characterized as tumor suppressors or oncogenes. Restoring the expression of tumor suppressor genes by epigenetic therapy has great potential in cancer treatment and it has been shown that some miRNAs can be directly regulated from their own promoters by epigenetic alterations in cancer cells. However, the majority of miRNAs are located within intronic regions of transcription units and it was unclear if intronic miRNAs can also be epigenetically regulated. Here we show that the tumor suppressor miR-126, which is located within an intron of the EGFL7 gene, is downregulated in cancer cell lines and in primary bladder and prostate tumors. Mature miR-126 can be generated from three different transcripts of EGFL7 with each one having its own promoter. Interestingly, miR-126 and one of the transcripts of EGFL7 that has a CpG island promoter are concomitantly upregulated in cancer cell lines by inhibitors of DNA methylation and histone deacetylation. These findings suggest that epigenetic changes can control the expression of tumor suppressor intronic miRNAs by directly controlling their host genes. Thus, epigenetic therapy not only directly activates miRNAs from their own promoters, but also activates intronic miRNAs together with their host genes. This reveals an additional mechanism and anticancer effect of epigenetic therapy.